2022
DOI: 10.25222/larr.73
|View full text |Cite
|
Sign up to set email alerts
|

The Architecture of Feminicide: The State, Inequalities, and Everyday Gender Violence in Honduras

Abstract: Increasing exclusion and inequality in Honduras have posed escalating security risks for women in their homes and on the streets. In this article, we examine gender-based violence against women, including gender-motivated murders (feminicides), the everyday acts that can result in their deaths, and impunity for these crimes. Rather than analyzing these murders as interpersonal acts or linking them to economic deprivation, we examine the actions and inactions of the state that have amplified violence in the liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 27 publications
(19 reference statements)
1
75
0
Order By: Relevance
“…Honduras endorses regional and international laws against violence, for example, criminalising intrafamily violence, rape and killings of women. However, these laws are weakly implemented or even omitted 36. Violence against women has intensified in Honduras caused by the deteriorating rule of law, escalating repression, and amplified gender-based violence targeting women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Honduras endorses regional and international laws against violence, for example, criminalising intrafamily violence, rape and killings of women. However, these laws are weakly implemented or even omitted 36. Violence against women has intensified in Honduras caused by the deteriorating rule of law, escalating repression, and amplified gender-based violence targeting women.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, other Central American countries, such as El Salvador and Guatemala, which also exhibit high levels of violence, have made relatively more progress than Honduras towards creating specialised services for women (eg, Ciudad Mujer in El Salvador and specialised feminicide courts in Guatemala). Similarly, Nicaragua and Costa Rica have relatively lower overall levels of violence and lower levels of feminicide 36…”
Section: Discussionmentioning
confidence: 99%
“…The women interviewed explained how, during demonstrations against the coup in 2009, military officials had harassed activists physically and verbally. Some had shouted at women to go home to their families, called them whores or threatened them with sexual violence (Menjívar & Walsh, 2017;Ronderos, 2011). Such verbal and physical violence had continued at demonstrations the activists had attended even in the years following the coup.…”
Section: Women's Bodies As Battlefields: Structural and Institutionalmentioning
confidence: 99%
“…Such verbal and physical violence had continued at demonstrations the activists had attended even in the years following the coup. Scholars have found that in Honduras, the legal and judicial system's actions and inactions have contributed to violence on women (Menjívar & Walsh, 2017). In addition to physical and verbal violence, activists interviewed reported that the post-coup regime had begun restricting women's reproductive rights, for example by prohibiting emergency contraception.…”
Section: Women's Bodies As Battlefields: Structural and Institutionalmentioning
confidence: 99%
“…In Latin American studies, the consensus that its democracies are weak requires more study of such weakness's sources, development, and impacts. 1 Many studies work to explain gaps between laws on paper and laws in practice (Menjívar and Walsh 2017). Through arms trafficking, this article advances such study on two levels: the weakness of democracy and the state on one level, and the trend toward iron fist (mano dura) policing on another.…”
mentioning
confidence: 96%